What Justifies Sustainable Finance Measures? Financial-Economic Interactions and Possible Implications for Policymakers - William Oman; Romain Svartzman (CESifo Forum, 2021)
Greening the economy is high on the political agenda. As early as 2015, the Paris Agreement set ambitious targets to combat climate change. Efforts have since become broader and are now aimed at promoting sustainable development in general, as set out in the UN 2030 Agenda for Sustainable Development. The financial sector is expected to play an important role in the upcoming transition towards a more sustainable economy. Therefore, policy makers in different parts of the world are developing "sustainable finance" programs. The EU Commission has just released a renewed sustainable finance strategy. This issue of CESifo Forum explores why sustainable finance programs may be necessary and takes a closer look at investor and corporate behavior. The authors assess how important the objective of sustainability has been so far and examine how it affects the decisions of companies and those of their peers. They also propose measures to render the corporate sector more sustainable.
Keywords: 330